PELATIHAN PENYUSUNAN KEBIJAKAN PENGEMBANGAN UMKM BAGI PEMERINTAH DAERAH KABUPATEN INDRAMAYU - Gunardi Lie; Jelita Damai Sofia Lorenza Sihite; Louis Sebastian Anot Putra; Stanley Muljadi Art (Jurnal Serina Abdimas, 2025)
Indramayu Regency has great potential in the development of Micro, Small, and Medium Enterprises (MSMEs) spread across various economic sectors. However, the contribution of MSMEs to regional economic growth is still relatively low due to the non-optimization of inclusive and pro-investment regional policies. Based on these conditions, this community service activity aims to increase the capacity of local government officials in designing MSME development policies that are data-based, participatory, and adaptive to local needs. The methods used include workshops, focus group discussions (FGDs), and simulations of drafting regulations, with a collaborative approach between academics, government, and business actors. It is expected that this activity can produce a policy framework that is more adaptive to the needs of the business world, improve the investment climate, and strengthen the role of MSMEs in sustainable regional economic development. The results of this activity include scientific publication articles indexed by SINTA or international journals, registration of intellectual property rights (IPR) for educational materials, and development of products or prototypes that support digital legal literacy. With this activity, it is hoped that the Indramayu government can be more aware of the law and can be more effective in formulating MSME development policies. ABSTRAK Kabupaten Indramayu memiliki potensi besar dalam pengembangan Usaha Mikro, Kecil, dan Menengah (UMKM) yang tersebar di berbagai sektor ekonomi. Namun, kontribusi UMKM terhadap pertumbuhan ekonomi daerah masih tergolong rendah akibat belum optimalnya kebijakan daerah yang inklusif dan pro-investasi. Berdasarkan kondisi tersebut, kegiatan pengabdian kepada masyarakat ini bertujuan untuk meningkatkan kapasitas aparatur pemerintah daerah dalam merancang kebijakan pengembangan UMKM yang berbasis data, partisipatif, dan adaptif terhadap kebutuhan lokal. Metode yang digunakan meliputi workshop, diskusi kelompok terfokus (FGD), dan simulasi penyusunan regulasi, dengan pendekatan kolaboratif antara akademisi, pemerintah, dan pelaku usaha. Diharapkan, kegiatan ini dapat menghasilkan kerangka kebijakan yang lebih adaptif terhadap kebutuhan dunia usaha, meningkatkan iklim investasi, serta memperkuat peran UMKM dalam pembangunan ekonomi daerah secara berkelanjutan. Hasil dari kegiatan ini mencakup artikel publikasi ilmiah terindeks SINTA atau jurnal internasional, pendaftaran hak kekayaan intelektual (HKI) atas materi edukatif, serta pengembangan produk atau prototipe yang mendukung literasi hukum digital. Dengan kegiatan ini, diharapkan pemerintah Indramayu dapat lebih sadar hukum dan dapat lebih efektif dalam menyusun kebijakan pengembangan UMKM .